The Determination of Single-phase Transformer No-load Losses; Information technologies and electrical engineering - device and systems, materials and technologies for the future - Goldstein (Goldshtein) E. I. Ephrem Iosifovich (Power Engineering, 2006)
Заглавие с титульного листа